2012
DOI: 10.1007/s00395-012-0285-1
|View full text |Cite
|
Sign up to set email alerts
|

Release of a humoral circulating cardioprotective factor by remote ischemic preconditioning is dependent on preserved neural pathways in diabetic patients

Abstract: Efficacy of ischemic preconditioning is decreased in animal models of type 2 diabetes mellitus while the responses in humans with diabetes are contradictory. It is unknown whether attenuation is related to decreased release of a mediating humoral cardioprotective factor or reduced ability to respond in the target tissue. The aim of the present study was to investigate the release and effect of a circulating cardioprotective factor in type 2 diabetes mellitus patients. Blood samples were drawn from nine non-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 31 publications
6
110
0
4
Order By: Relevance
“…Furthermore, the authors of this study did not demonstrate that their remote ischemic preconditioning protocol was effective in a younger nondiabetic population (Xu et al, 2014). In an intriguing clinical study by Jensen et al (2012) it was reported that diabetic patients with a peripheral neuropathy failed to produce a cardioprotective humoral factor in response to a standard remote ischemic preconditioning protocol (4 Â 5-minute upper arm cuff inflation/deflation) compared with nondiabetic and diabetic patients who did not have a peripheral neuropathy. This finding supports the notion that an intact neural pathway from/to the remotely conditioned organ or tissue is required to elicit the cardioprotective humoral factor (Jensen et al, 2012).…”
Section: Diabetesmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, the authors of this study did not demonstrate that their remote ischemic preconditioning protocol was effective in a younger nondiabetic population (Xu et al, 2014). In an intriguing clinical study by Jensen et al (2012) it was reported that diabetic patients with a peripheral neuropathy failed to produce a cardioprotective humoral factor in response to a standard remote ischemic preconditioning protocol (4 Â 5-minute upper arm cuff inflation/deflation) compared with nondiabetic and diabetic patients who did not have a peripheral neuropathy. This finding supports the notion that an intact neural pathway from/to the remotely conditioned organ or tissue is required to elicit the cardioprotective humoral factor (Jensen et al, 2012).…”
Section: Diabetesmentioning
confidence: 76%
“…Dissection of the individual contributions of these three sequential signaling steps has been an experimental challenge that remains unsolved. The current paradigm suggests that the conditioning stimulus within the remote organ or tissue generates autacoids, such as adenosine, bradykinin, and opioids, which result in the stimulation of the neural pathway to that remote organ or tissue (Liem et al, 2002;Jensen et al, 2012;Redington et al, 2012). The neural pathway then relays the cardioprotective signal to the brain stem nuclei (Lonborg et al, 2012), where a humoral factor(s), as yet unidentified, is released into the circulation and carried to the heart to mediate the cardioprotective effect.…”
Section: Cardioprotection Through Remote Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…180 However, patients with coronary artery disease have also been exposed to risk factors and comorbidities that increase the sensitivity to myocardial ischemia/ reperfusion injury and attenuate cardioprotective signaling, such as hypertension, 181,182 hypercholesterolemia, 183,184 and diabetes mellitus. [185][186][187][188][189] Patients with coronary artery disease have endothelial dysfunction. The endothelium, however, is important in mediating the cardioprotective effect of remote ischemic conditioning.…”
Section: Lack Of Comorbidities and Comedications In Animal Experimentsmentioning
confidence: 99%
“…15,16 The exact nature of the circulating cardioprotective factors released by RIPC remains unknown. RIPC by transient limb ischemia is dependent on intact neural pathways 17 and nitric oxide-sensitive nerve stimulation to release bloodborne, hydrophobic, and small (molecular mass <15 kDa) circulating factor(s), [18][19][20] modify the prosurvival kinase phosphatidylinositol 3-kinase (PI3K)-Akt and the mitogen-activated protein kinase p44/p42 extracellular signal-regulated kinase (ERK)1/2, glycogen-synthase kinase GSK-3β, 21 and STAT5 signaling 22 and finally converge at the mitochondrial level to prevent mitochondrial permeability transition pore opening in early reperfusion (Figure).…”
Section: Schmidt Et Al Remote Ischemic Preconditioning 1279mentioning
confidence: 99%